Pola Pembinaan Prestasi Pusat Pendidikan dan Latihan Pelajar (PPLP) Sepak Takraw Putra Jawa Tengah Tahun 2013 - Aji, Tri (Universitas Negeri Semarang, 2013)
The problem in this research is how coaching menÃ¢â¬â¢s sepak takraw PPLP achievement salatiga Central Java that include: builder, responsible person, organization, athlete, coach, coaching program, facilities and infrastructure and achievement. Research purposes to determine the achievement of coaching menÃ¢â¬â¢s sepak takraw PPLP in Salatiga in Central Java. Usefulness of the results of this study are expected to contribute information to an input for the development of sporting achievement and the development of sepak takraw sepak takraw sport in Central Java. Research uses descriptive qualitative research approach. Data collection using observation, documentation and interviews. Source of research data is 12 sepak takraw menÃ¢â¬â¢s athlete PPLP Central Java, 2 as coach of the menÃ¢â¬â¢s team sepak takraw Central Java, one of the managers organization. Model analysis of the data in this study used four interacting components, namely data collection, data reduction, data display, and conclusion. Results of research on the process of coaching menÃ¢â¬â¢s sepak takraw achievement PPLP Central Java in 2013 were 1) The state of menÃ¢â¬â¢s sepak takraw organization PPLP pretty good. 2) Quality has been good athletes based on the achievements. 3) Facilities and infrastructure are owned not complete, do not have a gym and fitness center sendri. 4) The coach who handles menÃ¢â¬â¢s sepak takraw PPLP in Salatiga Indonesia has been carrying the team in international Branch Office, has a national license and experienced. 5) The coaching program has been run in accordance with the planned program. 6) accomplishments achieved to date is excellent and always increase from year to year. Conclusions from this research is coaching menÃ¢â¬â¢s sepak takraw team achievements Central Java is a sports organization that is well structured and has good performance. Advice can be given, namely: Infrastructure for training should already have its own gym and not renting anymore. To increase game performance test that should be done more.